The Anti-Inflammatory Effects of Cannabidiol (CBD) on Acne - Peyravian N; Deo S; Daunert S; Jimenez JJ (Dove Medical Press, 2022)
Nadia Peyravian,1 Sapna Deo,1 Sylvia Daunert,1 Joaquin J Jimenez1,2 1Department of Biochemistry and Molecular Biology, University of Miami Miller School of Medicine, Miami, FL, USA; 2Phillip Frost Department of Dermatology & Cutaneous Surgery, University of Miami Miller School of Medicine, Miami, FL, USACorrespondence: Joaquin J Jimenez, Department of Biochemistry and Molecular Biology, University of Miami Miller School of Medicine, Miami, FL, USA, Tel +1 305 243 6586, Email j.jimenez@med.miami.eduAbstract: Acne is the most common skin condition in the United States and affects approximately 85% of people ages 12- 24. As a multifactorial disease, the pathogenesis of acne involves overproduction of sebum, irregular shedding of the cutaneous cells, accretion of Cutibacterium acnes at the pilosebaceous unit, and inflammation. To date, conventional therapies for acne include topical retinoids, over-the-counter bactericidal agents, and systematic treatments, such as oral antibiotics and isotretinoin. However, the potential for significant side effects and risk of antibiotic resistance remain limitations in these therapies, in turn reducing patient compliance and adherence to acne treatment regimens. Therefore, the use of natural plant-derived treatments or phytotherapeutics as an alternative or adjuvant to conventional treatments is attractive to patients due to their safety and minimal risk for side effects. Cannabidiol (CBD) is a non-psychoactive phytocannabinoid of the Cannabis sativa (hemp) plant. The therapeutic use of CBD has been implicated in many diseases with an inflammatory aspect, including cancers, neurodegeneration, immunological disorders, and dermatological diseases. However, the use of CBD for acne treatment remains a novel window of opportunity. Herein, we summarize the available and relevant data, highlighting the potential use of CBD in acne for its anti-inflammatory properties. To that extent, CBD and other cannabis constituents such as cannabis seeds were found to reduce inflammation and expression of inflammatory cytokines including TNF-α and IL-1β when evaluated in acne-like conditions. Treatment with these cannabis extracts was also found to be safe and well tolerated, further strengthening the prospect of CBD as an anti-inflammatory therapeutic for acne.Keywords: cannabidiol, CBD, acne, inflammation, therapeutic